Analisis Website Butik XYZ Menggunakan Google Search Console dan Google Analytics - Ayuningsih, Ekatri; Husna, Asmaul; Meuzaki, Ryezi; Panggabean, Jan Kevin (JURNAL RISET KOMPUTER (JURIKOM), 2025)
Butik Putri is a business in the fashion sector that sells its products through a website. A website is an application that contains various types of multimedia documents such as text, images, sound, animation, and video, used to provide information and introduce a product to the public broadly. To optimally increase the number of website visitors, an evaluation needs to be conducted by analyzing the website’s performance and visitor characteristics. The purpose of this study is to analyze the performance of the website and the characteristics of visitors to the Butik Putri website. The method used is a descriptive method. The research population consists of website visitors on the site Butik Putri from June to September 2025, totaling 620 people. Data collection techniques use secondary data from Google Search Console (GSC) and Google Analytics (GA). The results show that the website’s performance on search engine averages 2,2. The highest keyword search is “Butik Putri”. Indonesia is the country that accesses the website the most. Visitor characteristics increased with a total of 620 visitors. The most used browser is Chrome at 61,11%, the operating systems is Windows at 55,42%, and the device used is desktop at 61,11%. The website’s performance improved after adding Google Search Console (GSC) to the Butik Putri website. Along with that, visitor characteristics from Google Analytics (GA) data also increased but then decreased in the following month. To keep visitors continually increasing, website content must be continuously updated.